Symmetric Square Shaped Slotted Microstrip Antenna for RFID Applications - Ram D.; Khan A.; Singh A.K. (My University, 2025)
In this paper diagonally symmetrical slots with compact and small size are presented adapted in RFID reader handheld devices. There are diagonally equal square shaped slots present on top of radiating patch. The slots used here helped in bring out a tiny antenna for UHF RFID handheld reader devices. For the excitation of the radiating patch, simple coaxial feed is worn. The thorough bandwidth description of the proposed antenna is 29 MHz (883MHz-912MHz). The comprehensive size of antenna is 86 × 86× 4.6mm3. © 2021 IEEE.